COLLABORATIVE EFFORTS OF HEALTH INFORMATICS, MEDICAL SECRETARIES, DENTAL ASSISTANTS, NURSES, AND HEALTH ASSISTANTS IN ENHANCING PATIENT CARE DELIVERY: A MULTI-CENTER STUDY IN SAUDI ARABIA - Fatimah Aedh Bin Awdah Alanazi, Talea Shuayl Almutairi, Saud Wali Saket Aldhafeeri, Abdallah Kwikb Masir Aldafairi, Mona Jaber Aldhafeeri, Dhari Mamdouh Aldhaferi (Chelonian Research Foundation, 2022)
The healthcare system in Saudi Arabia has undergone significant reforms in recent years, with a focus on improving patient care and outcomes. Effective collaboration among healthcare professionals from various disciplines is crucial for achieving these goals. This study aimed to explore the collaborative efforts of health informatics specialists, medical secretaries, dental assistants, nurses, and health assistants in enhancing patient care delivery in Saudi Arabian healthcare facilities. A multi-center, cross-sectional design was employed, and data were collected through semi-structured interviews with 30 healthcare professionals from five different healthcare facilities in Saudi Arabia. Thematic analysis was used to analyze the data, and four main themes emerged: (1) roles and responsibilities, (2) interprofessional collaboration, (3) challenges and barriers, and (4) strategies for improvement. The findings highlight the essential roles these healthcare professionals play in providing quality patient care and suggest strategies for enhancing collaboration and overcoming barriers to effective patient care delivery. The study provides valuable insights for policy makers and healthcare organizations in developing strategies to support and empower interdisciplinary healthcare teams in Saudi Arabia. Keywords: collaboration, healthcare professionals, patient care, Saudi Arabia, qualitative research